Explaining E-Wallet Continuance Intention: A Modified Expectation Confirmation Model - Dhia, Afifah Wafir; Kholid, Muamar Nur (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2021)
This research paper aimed to examine the factors influencing user preferences to continue using E-Wallet. This research paper identified the factors by modifying the Expectation Confirmation Model by adding the Perceived Risk and Trust variables. This research paper employed primary data based on a questionnaire with a sample of E-Wallet users. Data were obtained by distributing online questionnaires, and data from 200 respondents were analyzed using Structural Equation Model – Partial Least Square (SEM-PLS). Data analysis indicated that Perceived Usefulness, Satisfaction, and Trust had a significant positive effect on users' intentions to continue using E-Wallet. On the other hand, confirmation had a positive and significant impact on perceived Usefulness and trust, while no effect on Satisfaction and Perceived Risk. Explanation and implications of data analysis are discussed.